Closing the gender gap in agriculture under climate change - Nyasimi, Mary; Huyer, Sophia (2017)
Women face barriers that significantly constrain their production and entangle them in a low productivity trap. These barriers encompass societal norms, the gender division of labour (GDOL), resource constraints (access to and use of land), no or low use of inputs (egdrought-adapted seeds), and limited access to climate services and agro-advisories. Under a changing climate, these barriers will further constrain women’s ability to adapt, and the gender gap in agriculture will continue to widen. Genderresponsive climate-smart agricultural (CSA) practices and technologies provide an opportunity to close the gender gap as well as bring women into the forefront in the fight against climate change. Priority activities include identification of the preferences and priorities of women, men and youth to develop practices that are appropriate to each group; labour-saving and productivity-enhancing technologies; access to climate information services; participation of women in agricultural value chains and non-farm activities; and engaging women and men in challenging social and cultural norms.